Kolb Interrupted : An investigation into students' experience of an experiential learning approach to entrepreneurship education - Marks, Jonathan Tresman (Department of Mechanical Engineering, 2014)
Entrepreneurial activity is widely regarded as a primary driver of socio-economic development. Alongside structural and systemic support, entrepreneurship education is a critical factor in improving entrepreneurial activity. While entrepreneurship education initiatives abound, little is understood about the effectiveness and pedagogical basis of these programmes, especially from the perspective of the student. This thesis focuses on a case study of a South African programme of entrepreneurship education designed around Kolb's Experiential Learning Cycle. The research employs a phenomenographic framework to identify the qualitatively different ways in which students experience this experiential learning approach to entrepreneurship education. This research shows that students' ways of experiencing learning can be characterised in one of two ways; a superficial way of experiencing learning in which students takes on a less sophisticated and surface view of learning, and an immersed way of experiencing learning in which students' engage in a deep and sophisticated manner. These ways of experiencing learning suggest two ways in which Kolb's Experiential Learning Cycle is interrupted; firstly, at the point of concrete experience, and secondly, at the point of reflective observation. This study makes a contribution to knowledge by examining experiential learning from the perspective of the student, and shows how programmes of entrepreneurship education can be better designed, in order to have an impact on entrepreneurial activity and socio-economic development.